Possibilidades para uma arquitetura habitável. O caderno. De arquivos e (des)encantos - Diana Maria Máximo Queirós (2018)
This dissertation represents a construction by the movement, for what we are under construction and how this demand can transform us into (became*) an experimental laboratory in invention. Its structure (unformed) and deve-lopment were based on the indetermination and reinvention of a proper move-ment in projection and project. Moved not so much by issues of functionality, but issues of gesture.For the retrospective and perspective of "what it is to be an architect" before even "becoming myself an architect", but above all, to understand what shapes me as a possible interpreter of the world and of life.There are no absolute truths, but enormous possibilities. Architecture inter-prets all these home-places of my own and of others, desires and bonds in crea-ting a space. The house, to have a house, to build a house, to "make houses" ... since I was little I heard that architects are able to realize that dream. There were always (initial and continuous) questions, thoughts, and actions that sus-tained an excitement achievable in a movement (of mine) archi + constructor.The concretion found meaning in the section, in the writing, in the models and in a magnetic effect was arranged in three founding points. The first represents a kind of sensitivity of the way of thinking, of a certain pulsation.The second point, in spinning thought also subdivided by three other mo-ments, by the object (in) formation, which are the seeds of approximation to the DNA under construction. By the models (in) formers that are engines of reference and last, of the framework to be and act. The third point, presented as a space of concretization about the place around me and what I am as a pla-ce, the world is creating places in dimension and in existence, translates a lear-ning with the world, with nature and the others.A transformative imaginary (investigation) through my spaces and reference stations as one who picks up, hands in his toolbox and carries on feeling able to arrange anything. Creating in trial-error a world of possibilities for a habitable architecture that observes, listens and tries to be close and in encounter.